Pseudohypacusis: False and Exaggerated Hearing Loss. - Peck, James E. (Plural Publishing Inc., 2014)
Examining the issue of feigned or exaggerated hearing loss (HL) in depth, this book provides a comprehensive review and analysis of the literature on the identification, management, and psychological issues pertaining to false and exaggerated hearing loss (FEHL).